Impact of Emotive Ads - Mahapatra, Sabina (Indian Journal of Marketing, 2007)
Our emotions play an important role throughout the span of our lives because they enrich virtually all of our waking moments with either a pleasant or an unpleasant quality. Cacioppo and his colleagues wrote that "emotions guide and enrich our life; they provide meaning to everyday existence; they render the valuation placed on life and property" (Cacioppo et. al. 2001), which also illustrates that the relationship with our physical world is emotional. It therefore doesn’t come as a surprise that consumer researchers have found that emotions evoked by products enhance the pleasure of buying, owning, and using them (Hirschman&Holbrook 1982). In addition, it has often been argued that the experiential or emotional quality of products is becoming more and more important for differential advantage in the marketplace because products are now often similar with respect to technical characteristics, quality, and price. In some purchase decisions, emotional responses may even be a decisive factor. Clearly, the ’fun of use,’ i.e. the fun one experiences from owning or using a product, belongs to this affective rather than to the rational domain. The difficulty in studying affective concepts as ’joy of use’ or ’fun of use’ is that they seem to be as intangible as they are appealing. Even more, rather than being an emotion as such, ’having fun’ is probably the outcome of a wide range of possible emotional responses. Imagine, for example, the fun one has when watching a movie. A person will experience all kinds of emotions, such as fear, amusement, anger, relief, disappointment, hope, etc. Instead of one isolated emotion, it is the combination of these emotions that contributes to the experience of fun.